2022
DOI: 10.1080/07391102.2022.2109754
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiomodelling of an essential mammalian protein: Transcription Termination Factor 1 (TTF1)

Abstract: Transcription Termination Factor 1 (TTF1) is an essential mammalian protein that regulates cellular transcription, replication fork arrest, DNA damage repair, chromatin remodelling etc. TTF1 interacts with numerous cellular proteins to regulate various cellular phenomena, and plays a crucial role in maintaining normal cellular physiology, dysregulation of which has been reported towards cancerous transformation of the cells. However, despite its key role in cellular physiology, the complete structure of human … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
4
9
0
Order By: Relevance
“…Deconvolution of spectra collected from CD and Raman spectroscopy shows that TTF1 is a helical protein, and this finding justifies its DNA-binding activity. The above finding is in agreement with our computational model for the full-length TTF1 as well . Previous publications reporting protein DNA atomic structures have shown that the DNA is stabilized between the helices of those proteins. , …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Deconvolution of spectra collected from CD and Raman spectroscopy shows that TTF1 is a helical protein, and this finding justifies its DNA-binding activity. The above finding is in agreement with our computational model for the full-length TTF1 as well . Previous publications reporting protein DNA atomic structures have shown that the DNA is stabilized between the helices of those proteins. , …”
Section: Resultssupporting
confidence: 92%
“…The secondary structure estimation after spectral deconvolution (as mentioned in the Materials and Methods section) gave estimated percentages of α helices (53.46%), β sheets (9.7%), random coils (23.78%), and turns (12.88%) (average of five runs, Table ), confirming the predominantly helical nature of the protein . The above finding is very much in agreement with our computational ab initio study and simulation data on human TTF1 protein …”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In this study, females had higher EGFR mutation rates than males, and never smokers had more EGFR mutations than ever smokers, which aligns with previous studies (15,22). Second, previous data had demonstrated, the positive expression of TTF-1 has a significant positive correlation with EGFR mutations in patients with LUADs, and if the expression of TTF-1 was negative, there was a 95% chance of wild-type EGFR mutation (17)(18)(19). In the current study, among 362 patients, there were 329 cases (92.3%) with the positive expression of TTF-1.…”
Section: Discussionsupporting
confidence: 90%